KONSEP DIRI, KEMATANGAN EMOSI DAN KECENDERUNGAN MENYONTEK - Risaniatin Ningsih; Herlan Pratikto (Jurnal Psikologi Tabularasa, 2012)
Abstract This research aims to find out the relationship between self-concept and emotional maturity with the tendency of cheating. This research is the kind of analytic research where its population totaled 1,516 quantitative people are students of class X, XI, and XII SMK PGRI 1 Kediri. The research was done by taking a sample of 125 students of class XI. Research data collected by using the tools in the form of three scales according the number of the variable self concept scale research i.e., scale of maturity and emotional tendencies scale cheated. After all the collected data, then do a test validity and reliability test to make sure that all the instruments used in this research worthy. Test results are all the instruments (scales) were declared invalid and reliabel. After that is done using the program correlation test with SPSS for windows release 16. The test results show that there is no correlation relationship between self-concept and tendency of cheating. Similarly, there is no relationship between emotional maturity with the tendency of cheating. Keywords: self concept, emotional maturity, the tendency of cheating